PEMEROLEHAN BAHASA PADA ANAK HOMESCHOOLING TAHAP PRAOPERASIONAL - Risqi Nor Cahyani (Jurnal Metrum, 2025)
This research discusses language acquisition in homeschooling children at the preoperational stage (2-7 years) based on Jean Piaget's theory of cognitive development. Children at this stage begin to develop symbolic thinking skills and use language to express themselves and understand their surroundings. Homeschooling as an educational alternative provides flexibility and personalization in learning, where the active role of parents determines the child's language development. A qualitative research method with a phenomenological approach was used to understand children's subjective experiences and the role of parents in the language acquisition process. Data were obtained through interviews with one of the resource persons named Mrs. Rifah, who acted as the main source in language acquisition in preoperational stage homeschooled children. The results show that homeschooled children acquire language skills gradually and meaningfully through intensive interaction with family and consistent language stimulation, such as shared reading activities and daily communication. The aspects of language that develop include vocabulary, phonology, morphology, syntax, and semantics. Although the language development of homeschooled children is quite good, there are challenges in social communication skills outside the family environment. This study emphasizes the importance of family support as the main foundation in early childhood language learning in homeschooling and recommends increasing social interaction to support children's communication skills more broadly.